Assessment of methods for predicting physical and chemical properties of organic compounds - Tunga Salthammer (Elsevier, 2024)
For the ecotoxicological assessment of a chemical substance it is important to know its partition behavior. In inanimate nature these are water, soil and air. Indoors it is gas and particle phase, settled house dust and surfaces. Due to the complex interaction of molecules with environmental compartments, their dynamics is usually modeled. However, this requires as precise information as possible about the physical and chemical properties as well as reaction pathways. Traditionally, the parameters necessary for the respective modeling are determined experimentally. However, with the increasing performance of computers, prediction tools based on structure-activity relationships and quantum mechanical calculations have become increasingly popular. The algorithms underlying the respective tools are highly specialized and mathematically sophisticated. Therefore, scientific expertise and extensive experience are needed to assess whether a specific value is reliable or not. This work provides an overview of available databases and prediction tools. It is intended to support the user in selecting accurate molecular parameters of organic substances in order to be able to make reliable statements about the partitioning of these substances in the indoor environment and about exposure of occupants.